TINJAUAN UMUM FORMULASI KEBIJAKAN TINDAK PIDANA PENDIDIKAN - Dewi Gangga, Juliani; Mas Aryani, Ni Nyoman (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 04, Juni 2013, 2013)
Paper shall be entitled "Analysis towards Educational Criminal Act Penal Policy". Education shall be regarded as the most strategic spectrum within national development. Up to this point, numerous criminal acts within the circumference of educational sphere had occurred. One of the occurrences shall be the emphasis on teacher’s marking mechanism and educational courses conduct commercially with no accordance towards the quality of the education itself. As stipulated within the national legislation act, Law No. 20 Year 2003 regarding National Educational System, it implied no clear definition regarding qualification of delict in educational aspect. Therefore, it urges the needs to classify vary of acts classified into educational criminal act. Penal policy formulation is seen as one of the essential efforts in overcoming related occurrences of educational criminal act.
Keywords: Policy Formulation, Criminal Act, Education